Ovarian morphology is a marker of heritable biochemical traits in sisters with polycystic ovaries. - Franks, S; Webber, L; Goh, M; Valentine, A; White, D; Conway, G; Wiltshire, S; McCarthy, M (2008)
CONTEXT: Polycystic ovary syndrome (PCOS) is a common endocrinopathy of uncertain etiology but with strong evidence for a genetic contribution. OBJECTIVE: The objective of the study was to test the hypothesis that the typical polycystic ovarian morphology is a marker of inherited biochemical features in families of women with PCOS. DESIGN: A study of probands with PCOS and their sisters. PATIENTS: Patients included 125 probands and 214 sisters. All probands had PCOS, defined by symptoms of anovulation and/or hyperandrogenism with polycystic ovaries on ultrasound. Affected sisters were defined by polycystic ovaries, regardless of symptoms, and unaffected sisters defined by normal ovarian morphology. SETTING: This was a clinic-based study. MAIN OUTCOME MEASURES: Clinical, endocrine, and metabolic features in the various groups were compared, and estimates of broad-sense heritability were obtained using the quantitative transmission disequilibrium test. RESULTS: Although affected sisters had fewer symptoms than probands (30% had no symptoms of PCOS), serum testosterone, androstenedione, LH, and fasting insulin and insulin sensitivity were similar in the two groups with polycystic ovaries but significantly different from those in unaffected sisters or controls. We observed moderate to high heritabilities for all traits studied in affected sister pairs, whereas heritabilities calculated from discordant siblings were substantially lower. CONCLUSIONS: These data provide further evidence for a genetic basis of PCOS. The high heritability of biochemical features in probands and affected sisters, despite wide variation in symptoms, shows that not only are these biochemical traits strongly influenced by genetic factors but also, importantly, that polycystic ovarian morphology is an index of inherited traits in families with PCOS.